ETOS KERJA KEPALA MADRASAH DI MADRASAH ALIYAH DARUL MU'ALLA SUNGAI ULAK NALO TANTAN KABUPATEN MERANGIN - Siti Aminah (UNISAN JURNAL, 2024)
The point of this exploration is to portray the hard working attitude of the Head of Mama Darul Mu'Alla Sungai Ulak Nalo Tantan. The point of this exploration is to decide the hard working attitude of the head of Mama Darul Mu'Alla Sungai Ulak Nalo Tantan. The kind of examination utilized is subjective illustrative exploration, to be specific an exploration system that produces enlightening information as composed or expressed words from individuals and entertainers being noticed. Information assortment methods in this examination are meetings, perception and documentation. The information examination system utilized in this exploration is subjective examination. In view of the discoveries of the examination and conversation, the exploration results can be reasoned that in regards to the hard working attitude of the Head of Madrasah Mama Darul Mu'Alla Sungai Ulak Nalo Tantan Merangin Regime as follows: First, discipline has been completed by the top of the madrasah, one of whom is managing and assessing the learning exercises did given to understudies in class, so educators don't recklessly give figuring out how to their understudies, this action means to understand the vision and mission wanted by the school. to accomplish. Second, the Head of the Madrasah has accomplished difficult work, this should be visible from the dedicated nature found in the advancement of the school since it was driven by the Head of the Madrasah, already this school had not fostered that much. Schools are progressively creating, this should be visible from the rising number of understudies and the rising number of foundation offices possessed by the school. Third, the Madrasah Head is entirely capable, this is viewed as never squandering the command given and working expertly and relatively without failing to remember the connection between one component and one more in the school. Fourth, the Head of Madrasah Mama Darul Mu'Alla Sungai Ulak Nalo Tantan Merangin Regime works with extraordinary pride in completing his obligations and his work will lead somebody to great amazing skill. Or possibly a feeling of adoration for what is done will develop so a Madrasah Head doesn't consider what he does as a weight.